PENENTUAN ORIGINAL GAS IN PLACE DENGAN METODE MATERIAL BALANCE ANALYSIS MENGGUNAKAN TEKANAN KEPALA SUMUR UNTUK SUMUR GAS BERTENAGA PENDORONG BOTTOM WATER DRIVE - Panji Reksaputra, Dimas
To calculate the Original Gas In Place (OGIP) using P/Z material balance method, production and reservoir pressure data are needed to do the analysis, whereas reservoir pressure data usally not measured regularly from time to time. This method will give good results if used for reservoir that does not have a driving mechanism, especially strong water or this method is used in very weak water drive, so the effect of driving mechanism can be neglected. In this study, the curve of P / Z vs. Gp was modicated from material balance equation by including parameters of water influx, water production, and compressibility. The pressure used in this study is the wellhead pressure. On the other hand, bottomhole pressure data is usally available, so it needed a method to calculate wellhead pressure using bottomhole pressure which is average temperature and compressibility factor method. Based on the results of the sensitivity test, an error obtained between OGIP’s simulation results and OGIP’s proposed P/Z methodby including parameters of water influx, production water, and compressibility, the largest error obtained was 15.45 % and 0.87 % for the smallest error. Seeing the considerable error generated, an error equation was made from all parameters of sensitivity test, after the error equation is validated, the results are quite satisfactory and the error equation can be used to obtain more accurate results OGIP after correction.